Personality and Developmental Characteristics of Primary School Students’ Personality Types - Yu, Yongjin; Zhang, Yanyan (Frontiers in Psychology, 2021)
The aim of the current study was to investigate the personality characteristics and developmental characteristics of primary school students’ personality types in a cross-sectional sample of 10,366 Chinese children. The Personality Inventory for Primary School Student was used to evaluate primary school students’ personality. Latent profile analysis (LPA) was used to classify primary school students’ personality types. One-way ANOVA was used to explore the personality characteristics of personality types, and Chi-square tests were used to investigate grade and gender differences of primary school students’ personality types. Results showed that the primary school students could be divided into three personality types: the resilient, the overcontrolled, and the undercontrolled. Resilients had the highest scores, and undercontrollers had the lowest scores on all of five personality dimensions (intelligence, conscientiousness, extraversion, agreeableness, and emotional stability). The overcontrollers’ scores on personality were between the other two types, with lower emotional stability. As the grade level increased, the proportion of undercontrolled students in primary schools generally showed an upward trend and reached the maximum in grade 5. The proportion of resilient students in primary schools generally showed a downward trend. The proportion of resilient students was highest in grade 2 and lowest in grade 5. Girls were significantly more likely than boys to be resilient personality types, while boys were significantly more likely than girls to be undercontrolled personality types. The overcontrolled personality type did not show significant gender differences. Because of the undesirable internalizing problems related to overcontrollers and the externalizing problems related to undercontrollers, our results have implications for Chinese schools, families, and society in general.